Modelling silicosis: Existence, uniqueness and basic properties of solutions. (August 2021) - da Costa, Fernando P.; Pinto, João T.; Sasportes, Rafael
Abstract: We present a model for the silicosis disease mechanism following the original proposal by Tran et al. (1995), as modified recently by da Costa et al. (2020). The model consists in an infinite ordinary differential equation system of coagulation–fragmentation–death type. Results of existence, uniqueness, continuous dependence on the initial data and differentiability of solutions are proved for the initial value problem.